Determination of Antioxidant activities of locally produce rice in Northern and Western part of Nigeria, using Kebbi rice and Igbemo rice as case study - Ugwo, Jeremiah; Adealawode , Marvellous Kehinde (Catalyx : Journal of Process Chemistry and Technology, 2024)
This research provides the antioxidant activities of locally produced rice in the Northern and Western regions of Nigeria, with a focus on Kebbi rice and Igbemo rice. The study utilizes the Ferric Reducing Antioxidant Power (FRAP) and 2,2-Diphenyl-1-picrylhydrazyl (DPPH) assays to evaluate the antioxidant capacity of these rice varieties. In which the sample was extracted using solvent extraction method after which the antioxidant (AO) activity of the rice samples as ferric-reducing power, is determined using a modified FRAP (ferric reducing/antioxidant power) assay Sodium phosphate, buffer solution, pipettes, test tubes, centrifugal machine, TCA, KFC and reagent such as Fe(iii) solution were used to analyse the ferric reducing antioxidant power (FRAP) of the sample. Also, Methanolic solution, and spectrophotometer to measure absorbance at 516nm is used to determine the free radical scavenging ability of the extract against DPPH (1, 1- diphenyl-2-picryhydrazyl). Results reveal that Kebbi rice exhibits higher FRAP values compared to Igbemo rice, indicating superior antioxidant activity in the FRAP assay. Conversely, Igbemo rice demonstrates higher DPPH values than Kebbi rice, suggesting greater antioxidant potency in the DPPH assay. These findings underscore the variability in antioxidant properties among different rice varieties and highlight the importance of considering multiple assays for a comprehensive assessment of antioxidant activity. Understanding the antioxidant profiles of indigenous rice varieties like Kebbi and Igbemo rice is crucial for promoting their consumption and enhancing food security in Nigeria. Further research is warranted to elucidate the specific antioxidant compounds responsible for the observed differences and explore their potential health benefits.